(untitled) (Faridpur Medical College Journal, 2019)
Acyclovir has well-documented efficacy and tolerability in the treatment of herpes zoster. Its limited oral bioavailability and short half-life, however, necessitates frequent dosing. Valacyclovir, the l-valyl ester of acyclovir, could be rapidly converted to acyclovir after oral administration, resulting in a three to five fold increase in acyclovir bioavailability compared with oral acyclovir in humans. The study was done in the department of Dermatology and Venereology, Faridpur Medical College Hospital (FMCH), Faridpur, Bangladesh from July 2015 to December 2016 to compare the safety and efficacy of valacyclovir with acyclovir in the treatment of herpes zoster. Relevant data was taken from 50 patients presenting with herpes zoster within 72 hours after the onset of rash and were randomized into two groups of 25 each to receive one of the following treatments: valacyclovir 1000 mg three times daily for 7 days or acyclovir 800 mg five times daily for 7 days for each group. Patients were followed up on day 7, 14, 22 and 29 to assess the rate of resolution of pain, cessation of abnormal sensations, rate of rash healing, new lesion formation and occurrence of complications or adverse effects. The intent-to-treat analysis showed that valacyclovir significantly accelerated the resolution of zoster-associated pain compared with acyclovir; on day 29, the valacyclovir group was 44% superior to the acyclovir group. The rate of cessation of abnormal sensations, rash healing and complications or adverse effects was similar with both the treatments. There were no clinically significant differences in the nature, frequency or severity of adverse events between the two treatment groups. Thus, we conclude that in the management of herpes zoster, valacyclovir accelerates the resolution of pain and offers a simpler dosing, and maintains the favorable safety profile of acyclovir. Faridpur Med. Coll. J. Jul 2018;13(2): 74-77